Effects and Mechanisms of Surface Topography on the Antiwear Properties of Molluscan Shells (Scapharca subcrenata) Using the Fluid-Solid Interaction Method - Limei Tian; Ximei Tian; Guoliang Hu; Yinci Wang; Luquan Ren (The Scientific World Journal)
The surface topography (surface morphology and structure) of the left Scapharca subcrenata shell differs from that of its right shell. This phenomenon is closely related to antiwear capabilities. The objective of this study is to investigate the effects and mechanisms of surface topography on the antiwear properties of Scapharca subcrenata shells. Two models are constructed—a rib morphology model (RMM) and a coupled structure model (CSM)—to mimic the topographies of the right and left shells. The antiwear performance and mechanisms of the two models are studied using the fluid-solid interaction (FSI) method. The simulation results show that the antiwear capabilities of the CSM are superior to those of the RMM. The CSM is also more conducive to decreasing the impact velocity and energy of abrasive particles, reducing the probability of microcrack generation, extension, and desquamation. It can be deduced that in the real-world environment, Scapharca subcrenata’s left shell sustains more friction than its right shell. Thus, the coupled structure of the left shell is the result of extensive evolution.